Fabrication of Poly Dopamine@poly (Lactic Acid-Co-Glycolic Acid) Nanohybrids for Cancer Therapy via a Triple Collaboration Strategy - Yunhao Li; Yujuan Gao; Zian Pan; Fan Jia; Chenlu Xu; Xinyue Cui; Xuan Wang; Yan Wu (Nanomaterials, 2023)
Breast cancer is a common malignant tumor among women and has a higher risk of early recurrence, distant metastasis, and poor prognosis. Systemic chemotherapy is still the most widely used treatment for patients with breast cancer. However, unavoidable side effects and acquired resistance severely limit the efficacy of treatment. The multi-drug combination strategy has been identified as an effective tumor therapy pattern. In this investigation, we demonstrated a triple collaboration strategy of incorporating the chemotherapeutic drug doxorubicin (DOX) and anti-angiogenesis agent combretastatin A4 (CA4) into poly(lactic-co-glycolic acid) (PLGA)-based co-delivery nanohybrids (PLGA/DC NPs) via an improved double emulsion technology, and then a polydopamine (PDA) was modified on the PLGA/DC NPs’ surface through the self-assembly method for photothermal therapy. In the drug-loaded PDA co-delivery nanohybrids (PDA@PLGA/DC NPs), DOX and CA4 synergistically induced tumor cell apoptosis by interfering with DNA replication and inhibiting tumor angiogenesis, respectively. The controlled release of DOX and CA4-loaded PDA@PLGA NPs in the tumor region was pH dependent and triggered by the hyperthermia generated via laser irradiation. Both in vitro and in vivo studies demonstrated that PDA@PLGA/DC NPs enhanced cytotoxicity under laser irradiation, and combined therapeutic effects were obtained when DOX, CA4, and PDA were integrated into a single nanoplatform. Taken together, the present study demonstrates a nanoplatform for combined DOX, CA4, and photothermal therapy, providing a potentially promising strategy for the synergistic treatment of breast cancer.